2019
DOI: 10.1111/tbed.13154
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐quantitative duplex RTPCR reveals the low occurrence of Porcine Pegivirus and Atypical Porcine Pestivirus in diagnostic samples from the United States

Abstract: SummaryPorcine Pegivirus (PPgV) and Atypical Porcine Pestivirus (APPV) are two recently identified porcine viruses. In this study, the identification of two viruses by metagenomic sequencing, and a duplex semi‐quantitative RT‐PCR was developed to detect these pathogens simultaneously. The PPgV strain Minnesota‐1/2016 had a 95.5%–96.3% nucleotide identity and clustered with the recently identified US PPgV strains, which is a distant clade from the German PPgV strains. The APPV strain Minnesota‐1/2016 shared an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
1
10
0
2
Order By: Relevance
“…For Germany, Beer et al [15] reported a genome prevalence of 9% in slaughter pigs and 20% in sera derived from farms whilst Kaufmann et al [21] detected a higher seroprevalence (13%) in slaughter pigs than in breeding pigs (<1%) in Switzerland. Semen samples and preputial swabs of commercial boar farms in the USA tested positive in 15.8% [28] and this number is in good accordance with the 16.4% genome detection rate reported by Chen et al [44] for the USA. Interestingly, a seroprevalence of 52% and a genome detection rate of 19% was determined for wild boar samples from Germany [23], indicating a wide spread of the pathogen also in wild populations.…”
Section: Phylogeny and Geographic Distribution Of Atypical Porcine Pestivirusessupporting
confidence: 90%
“…For Germany, Beer et al [15] reported a genome prevalence of 9% in slaughter pigs and 20% in sera derived from farms whilst Kaufmann et al [21] detected a higher seroprevalence (13%) in slaughter pigs than in breeding pigs (<1%) in Switzerland. Semen samples and preputial swabs of commercial boar farms in the USA tested positive in 15.8% [28] and this number is in good accordance with the 16.4% genome detection rate reported by Chen et al [44] for the USA. Interestingly, a seroprevalence of 52% and a genome detection rate of 19% was determined for wild boar samples from Germany [23], indicating a wide spread of the pathogen also in wild populations.…”
Section: Phylogeny and Geographic Distribution Of Atypical Porcine Pestivirusessupporting
confidence: 90%
“…In the United States, APPV was first identified by NGS in pig serum samples collected in 2014 from five different states [ 1 ]. In subsequent years, several studies from different countries reported the circulation of APPV in the US [ 1 , 2 , 51 , 54 , 56 ], Germany [ 53 , 55 , 57 , 58 , 59 , 60 , 61 ], Netherlands [ 10 ], Sweden [ 62 ], Austria [ 50 ], England [ 63 ], China [ 38 , 42 , 44 , 46 , 47 , 61 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ], Spain [ 41 , 74 ], South Korea [ 75 ], Brazil [ 16 , 48 , 49 , 76 ], Great Britain [ 61 ], Italy [ 43 , 61 ], Serbia [ 61 ], Switzerland [ 61 , 77 ], Taiwan [ 61 ], Canada [ 52 ], and Hungary [ 78 ].…”
Section: Atypical Porcine Pestivirusmentioning
confidence: 99%
“…APPV was first discovered from the serum of a pig without clinical symptoms in the United States (Hause et al, 2015). Since then, APPVs have been found from pigs and wild boars with or without CT worldwide on four continents, and genomic sequence diversity among APPVs has been reported (Beer et al, 2017;Cagatay et al, 2018;Chen et al, 2019;Choe et al, 2020;Colom-Cadena et al, 2018;de Groof et al, 2016;Dénes et al, 2018;Dessureault et al, 2018;Gatto et al, 2018;Mósena et al, 2018;Muñoz-Gonzalez et al, 2017;Pan et al, 2019b;Possatti et al, 2018;Postel et al, 2016Postel et al, , 2017Schwarz et al, 2017;Shen et al, 2018;Sozzi et al, 2019;Stenberg et al, 2020;Xie et al, 2019;Yan et al, 2019;Yuan et al, 2017;Zhang et al, 2017;Zhang et al, 2019;Zhou et al, 2019). However, genome sequence data of APPV have not been reported from Japan.…”
Section: Introductionmentioning
confidence: 99%